THE ASSESSMENT OF THE EFFECTS OF FLOODING IN GWANGE, MAIDUGURI METROPOLIS, BORNO STATE NIGERIA - MAHMUD, S.B; WAZIRI, M.; ABUBAKAR, S.Y.; ADADU, M.O.; HENNA, C.B. (Nigerian Journal of Fisheries, 2024)
Human activities such as rapid industrialization and urbanization, population growth, exploitation of natural resources and location of infrastructures have heightened the occurrence of floods. According to the United Nations Environment Program, flood is one of the major environmental crises ravaging the world today. The assessment of the effects of flooding in Gwange, Maiduguri Metropolis was carried out with the aim to identify the causes of flooding in Gwange, accessing the effects of flooding in the study area and examining the coping strategy adopted by the people of Gwange. Random sampling technique was applied for this study in Gwange with 125 respondents (householders) who were administered questionnaires. Flood had serious consequences on Gwange. The result of this finding showed that poor drainage and improper waste disposal (52.8%) were the major causes of flooding in Gwange. The finding also showed that Gwange has developed various means to mitigate the effects of flooding for the past five years such as increasing the foundation of their buildings, regularly clearing the drainage channels and placing of sandbags on affected roads. As recommendations, seminars and enlightenment campaigns should be organized frequently to educate the general public on ways of controlling flooding, encourage community participation and ameliorate the suffering of flood victims.